2018
DOI: 10.1038/s41598-018-20982-1
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Cataract in Children in Eastern China: Shanghai Pediatric Cataract Study

Abstract: Traumatic cataract is a main cause of visual impairment in pediatric populations and is preventable. Awareness of the causes and consequences of pediatric eye trauma play roles in health education and prevention of blindness. We conducted a retrospective chart review based on 5-year clinical data of pediatric traumatic cataract cases treated at the Eye and Ear, Nose and Throat Hospital of Fudan University, Shanghai, China. Clinical features including demographic data, injury mechanism, and causative agents wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
4
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 20 publications
5
29
4
2
Order By: Relevance
“…Our finding was consistent with previous reports [13,15,16,21,22] on children ocular trauma that penetrating injury caused by sharp objects had absolute predominance. Other causes include wooden stick, firecrackers, recreational activities and accidental domestic injuries.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our finding was consistent with previous reports [13,15,16,21,22] on children ocular trauma that penetrating injury caused by sharp objects had absolute predominance. Other causes include wooden stick, firecrackers, recreational activities and accidental domestic injuries.…”
Section: Discussionsupporting
confidence: 94%
“…The ratio of male to female was 4.3:1 (99 males and 23 females) in this study, higher than the sex ratio of 1.18:1 derived from the latest available census data in China [13]. Moreover, many studies reported a higher incidence of trauma in males than in females [7,9,[13][14][15][16], showing an average male-to-female ratio which ranged between 1.2:1 and 5.2:1. In our study, the male to female ratio was increased as patients grew, which was consistent with a study conducted by Yu Du et al [13] in Shanghai, China.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…However, it has been reported that 90% of eye injuries are preventable; therefore, identification of the frequency and spectrum of these injuries in a defined population and targeted educational and legislative efforts may be useful tools to minimize the incidence of eye injuries [7]. The epidemiology surrounding eye injuries has been reported in Beijing, Shanghai, Guangzhou, Chaoshan and Zhengzhou [8,9]. However, there is not enough data to compare rates in the United States, Europe, and Australia, especially for pediatric populations.…”
Section: Introductionmentioning
confidence: 99%
“…Mereka mengatakan bahwa kebanyakan pasien dengan trauma tumpul tidak mengingat penyebab traumanya karena terkena secara tiba-tiba saat melakukan aktivitas di luar ruangan. 7 Memon dkk juga menunjukkan hasil serupa pada studi yang dilakukan di populasi umum dimana benda penyebab tersering dari katarak traumatika adalah benda tajam dengan persentase 68,3%, mereka menjelaskan hasil ini disebabkan karena kebanyakan sampel mereka adalah anak-anak hingga dewasa muda dan hanya 24,4% sampel mereka adalah dewasa. 8 Visus yang ditemukan kebanyakan adalah 1/300.…”
Section: Pembahasan Karakteristik Katarak Taumatikaunclassified